Konsep Kurikulum Pendidikan dalam Perspektif Az-Zarnûjî: Studi Atas Kitab Ta’lîm Al-Muta’allim Tharîq At-Ta’allum - Ahmad Solihin (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2021)
This paper discusses the existence of the educational curriculum as a thought of al-Imam Buhan al-Islam az-Zarnûjî in the book Ta'lîm al-Muta'allim Tharîq at-Ta'allum. The focus of this paper examines the description of the concept and the steps that should be taken by educators and students in learning. This writing method is the historical method. While the approach used is a descriptive qualitative approach with the type of research Library Research (library research) which seeks to describe a variable in the form of symptoms or conditions according to what is in primary and secondary data sources. The results of research on the book Ta'lîm al-Muta'allim Tharîq at-Ta'allum by az-Zarnûjî which outlines 13 chapters, essentially discusses knowledge and acquires it based on strict religious ethics with the involvement of teachers, fellow students and their environment. The thought of az-Zarnûjî will bring up the characteristics of an educational curriculum that prioritizes religious ethics (allogical) with learning techniques that are socio-cultural and psychological-educational.